PURIFIKASI PARSIAL DAN KARAKTERISASI ENZIM KATEPSIN DARI IKAN BANDENG (Chanos Chanos Forskall) - Tati Nurhayati; Ella Salamah; nico Dynnar (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Decomposition of protein in the enzymatic process will lead to changes in odor, texture, and appearance of fish. The enzymes that play a role in the enzymatic process is primarily proteolytic enzymes. Cathepsin enzyme is one of the proteolytic enzymes found in animal tissue that hydrolyzes peptide bonds of proteins. Information on optimal conditions of cathepsin enzyme activity is useful in the process of good handling, to avoid environmental conditions that can increase cathepsin enzymes activity, especially in milkfish. The purposes of this study were to partial purify the catepsin enzyme of milkfish and characterize the enzymes. Crude extract of enzyme had specific activity 0.8598 U/mg and after presipitation with ammonium sulphate 70% obtained specific activity of 4.4643 U/mg and after 6 hours of dialysis obtained specific activity 14.4404 U/mg. The enzyme cathepsin worked optimally at 40 °C and pH 4, and 3% substrate. Divalent metal ions inhibited the activity of the enzyme, higher compared to monovalent or trivalent metals. Cathepsin enzyme identified had molecular weight of 86.67 kDa.Key words: cathepsin, characterization, milkfish, purification